Spelt as a Genetic Resource for Yield Component Improvement in Bread Wheat. Issue 6 (1st November 2015) - Xie, Quan; Mayes, Sean; Sparkes, Debbie L.
ABSTRACT: Novel germplasm resources are required to broaden the genetic diversity of bread wheat ( Triticum aestivum L.) for further yield improvement. In this study, the usefulness of spelt ( T. spelta L.) as a genetic resource to improve yield components of bread wheat was determined. A recombinant inbred line mapping population of bread wheat Forno and spelt Oberkulmer was used to quantify the yield components. Subsequently, quantitative trait loci (QTL) for yield components, together with grain threshability traits, were identified. Oberkulmer had larger grains (in 2012 season), more fertile tillers, higher biomass, longer and laxer spikes than Forno. Quantitative trait locus analysis revealed six alleles for low threshability and two for tenacious glumes from the spelt, and the Q gene had major effects. Furthermore, 40 favorable alleles for yield components were detected from Oberkulmer, and 83% of them were independent of those for low threshability and tenacious glumes. Therefore, spelt is a useful genetic resource for yield component improvement of bread wheat, while maintaining the free‐threshing habit. In addition, most of QTL for grain number components were coincident with those for grain weight. Allelic analysis of the coincident QTL showed that increased grain number was associated with decreased grain weight, which explained their negative phenotypic relationships.